Analisis Indeks Pembangunan Manusia Pulau Jawa Tahun 2010-2020 Dengan Pendekatan Panel Seemingly Unrelated Regression - Ariani, Khairina Putri; Kurniawan, Mahrus Lutfi Adi; Apriliana, Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The quality of Human Resources is the main factor in driving development. To measure the welfare of society as seen from several components, including health, education and living standards, it can be determined from the value of the Human Development Index (HDI). This research aims to analyze the influence of the number of poor people, economic growth, TPT, UMP, government spending in the education and health sectors on the Human Development Index (HDI) in provinces on the island of Java in 2010-2020. Through panel data regression using the Seemingly Unrelated Regression (SUR) analysis method model with Stata.14 processing, the results of this study show that (1) the number of poor people has a negative effect on HDI, (2) economic growth has a negative effect on HDI, (3) TPT negative effect on HDI (4) UMP has no effect on HDI, (5) government spending in the education sector has a positive effect on HDI (6) government spending in the health sector has no effect on HDI (7) number of poor people, economic growth, TPT, UMP, government spending the education and health sectors together have an influence on the provincial Human Development Index (HDI) on the island of Java for 2010-2020.